THE PROTECTIVE EFFECT OF TURMERIC RHIZOMES EXTRACT FROM HEPATOTOXICITY AND NEPHROTOXICITY INDUCED BY INDOMETHACIN - GHADA HASSAN; NAHLA IBRAHIM; AKIL HAJJOUZ (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: This study was conducted to investigate the effect of the ethanolic extract of turmeric rhizomes (Curcuma longa)on reducing hepatotoxicity and nephrotoxicity induced by Indomethacin in male white mice (the Balb-c strain), and to examine its potential in mitigating the side effects of this drug. Methods: Mice were randomly divided into four groups (10 mice/group). The first group (G1) was dosed with dimethyl sulfoxide (DMSO) 10%. The second group (G2) was given only turmeric rhizome extract dissolved in DMSO 10%. The third group (G3) was dosed with one dosage (166 mg/kg) of Indomethacin drug for 6 h. The fourth group (G4) was dosed with a dosage (300 mg/kg) of turmeric rhizome extract for 30 days then was dosed a dosage (166 mg/kg) of Indomethacin after 6 h. Serum levels of creatinine, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and lactate dehydrogenase (LDH) were measured, and a histological study of the livers and kidneys was performed. Results: Results showed a significant increase in liver enzymes (AST and ALT), LDH, and creatinine in G3 (477 U/L, 942 U/L, 5323 U/L, and 1.37 mg/dl, respectively), compared to G1 (41, 48, 455, and 0.63, respectively), while observed reduction in those biochemical parameters in G4 (63, 102, 1625, and 0.82, respectively). Results also showed the ability of turmeric rhizome extract (300 mg/kg) to decrease the pathological changes induced by indomethacin in the liver and kidney, as severe degenerative changes, Necrotic single cells, and vascular congestion. Conclusion: This study showed the important role of the ethanolic extract of turmeric rhizome in keeping the tissue structure of each liver and kidney safe from oxidative stress established by Indomethacin.